PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BAGIAN INSTALASI GAWAT DARURAT (IGD) RSU MAYJEN H.A. THALIB - Nora Aprianti (Ebisma (Economics, Business, Management, & Accounting Journal), 2021)
This research was conducted to determine the effect of leadership and work motivation on employee performance on the part of RSU Mayjen H.A Thalib Emergency Room (IGD) Kab. Kerinci. The data analysis method used is quantitative analysis by using multiple regression linier: F-test, Determination Coefficient, t-test. The study found that leadership and work motivation simultaneously affect the performance of employees at the Emergency Room (IGD) RSU Mayjen H.A Thalib, Kab. Kerinci. However, partially the only variable that has a significant effect is work motivation and also the most dominant variable